Flora of Bahia: Vitex Tour. ex. L. Lamiaceae - Lima, Carla Teixeira de; França, Flávio (SITIENTIBUS série Ciências Biológicas, 2009)
The genus Vitex is characterized by digitated compound leaves, bilipped corolla, didynamous androecium, axial placentation and drupaceous fruit. This study aimed at goals the inventory of Vitex species within the state of Bahia. There are 15 species in the state: Vitex agnus-castus, V. capitata, V. cymosa, V. flavens, V. gardneriana, V. hypoleuca, V. martii, V. megapotamia, V. mexiae, V. orinocensis, V. polygama, V. rufescens, V. schaueriana, V. sellowiana, and V. triflora.